1988
DOI: 10.1111/j.2042-3306.1988.tb01536.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of detomidine (Domosedan) on the maintenance of equine pregnancy and foetal development: ten cases

Abstract: Summary Detomidine was administered throughout 10 pregnancies in eight mares. An intravenous injection of 20 pg/kg bodyweight was given weekly from Day 14 to Day 60 of gestation and thereafter every four weeks until parturition. One mare suffered torsion of the large colon and was destroyed on Day 86; the foetus was normally developed. A further mare aborted at 167 days. The remaining eight pregnancies continued to full term. One foal was delivered by caesarean section because of torticollis and, of the seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In cattle, xylazine increases intrauterine pressure and is believed to have abortigenic capabilities [87]. In horses, no specific effects of the drug were detected in eight mares given 20 lg/kg/wk from day 14 to day 60 of gestation and then every 4 weeks until parturition [80]. Similarly, repeated detomidine doses caused temporary (90-minute duration) decreases in fetal heart rates but had no observed detrimental effects on the pregnancy [96].…”
Section: Broodmares and Neonatesmentioning
confidence: 95%
“…In cattle, xylazine increases intrauterine pressure and is believed to have abortigenic capabilities [87]. In horses, no specific effects of the drug were detected in eight mares given 20 lg/kg/wk from day 14 to day 60 of gestation and then every 4 weeks until parturition [80]. Similarly, repeated detomidine doses caused temporary (90-minute duration) decreases in fetal heart rates but had no observed detrimental effects on the pregnancy [96].…”
Section: Broodmares and Neonatesmentioning
confidence: 95%
“…Special concern has been raised about the capture and immobilisation of pregnant females, as drugs may reduce reproductive output and survival rate of offspring. Indeed, α2-agonists drugs were observed to affect bovine uterine contractility [ 39 ], and repeated doses were reported to cause abortion in horses [ 40 ]. Sakamoto et al [ 41 ] found that administration of xylazine to pregnant goats results in an alteration of the physiological parameters of both mother and foetus (i.e., decrease in uterine blood flow caused by the induction of uterine contractions, decrease in circulating blood volume, hypoxemia and acidosis in the mother) that may lead to abortion.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant mares, uterine electrical activity remained constant or decreased (Jedruch et al 1989). No consistent effects on the outcome of pregnancy were observed in a study in which detomidine was frequently administered to pregnant mares (Katila and Oijala 1988). However, only 6 foals were weaned from 10 pregnancies, but no similarities were noted between the other 4 cases.…”
Section: Introductionmentioning
confidence: 92%